What is the length of a straight line between the school and the fire station? Round to the nearest tenth.
Part B
The hospital is 3.1 miles west of the fire station. What is the length of a straight line between the school and the hospital? Round to the nearest tenth.
Answer:
a. The length of a straight line between the school and the fire station is 4.6 miles
b. The length of a straight line between the school and the hospital is 2.1 miles
Step-by-step explanation:
See attachment
Given.
Distance between the school and the town hall = 4.3 miles directly east
Distance between the fire station and the town hall = 1.7 miles directly north.
The length of a straight line between the school and the fire station is calculated by solving the length of hypotenuse of the right angled triangle (see attachment A)
Using Pythagoras theorem;
x² = 1.7² + 4.3²
x² = 2.89 + 18.49
x² = 21.38 --- Take square roots
x = 4.6 miles
The length of a straight line between the school and the fire station is 4.6 miles
b.
The length of a straight line between the school and the hospital is calculated by solving the length of hypotenuse of the right angled triangle (see attachment B)
Using Pythagoras theorem;
x² = 1.7² + 1.2²
x² = 2.89 + 1.44
x² = 4.33 --- Take square roots
x = 2.1 miles
The length of a straight line between the school and the hospital is 2.1 miles
Answer:
x = 5y over 3y-5
y = 5x over 3x-5
hope this helps
(x+2y=6 estimate the solution to the system of equations
Answer:
x=4/3; y=7/3
Step-by-step explanation:
x+2y=6,
x=6-2y.
7(6-2y)-y=7,
42-14y-y=7,
15y=35,
y=7/3.
x+2y=6,
x+2*7/3=6
x=4/3
∴x=4/3, y=7/3.
To estimate the solution to the system of equations (7x-y=7) and (x+2y=6), we can use the method of substitution. The estimated solution is x = 1.46 and y = 2.27.
To estimate the solution to the system of equations (7x-y=7) and (x+2y=6), we can use the method of substitution. We can solve one equation for one variable and substitute it into the other equation. Let's solve the second equation for x: x = 6 - 2y.
Substituting this value of x into the first equation, we get:
7(6 - 2y) - y = 7
42 - 14y - y = 7
41 - 15y = 7
-15y = 7 - 41
-15y = -34
y = -34 / -15
y = 2.27
Now, substitute this value of y back into the second equation to find x:
x + 2(2.27) = 6
x + 4.54 = 6
x = 6 - 4.54
x = 1.46
Therefore, the estimated solution to the system of equations is x = 1.46 and y = 2.27.
#SPJ2